Tangible and Intangible Values of Atatürk Forest Farm as a Heritage of Ideas - Selin Çavdar Sert (Ankara Araştırmaları Dergisi, 2017)
Within the shared boundaries of various disciplinary domains, there are a substantial number of studies dealing with the history of the establishment and socio-spatial values of Atatürk Forest Farm. The area is represented through the semantic field related to the venerable memory of Mustafa Kemal Atatürk and his heritage of ideas; the social, cultural and spatial goals of the republican revolution; the principles and procedures of being a modern and self-sufficient society; and the history of the establishment of Ankara as a capital. The Atatürk Forest Farm also comprises tangible cultural assets and natural systems – which transcend the borders of the site. Yet, there has not been any study identifying and associating the tangible and intangible values of the farm in a comprehensive way. This study aims to draw a layout for interdisciplinary conservation scenarios that would place the tangible and intangible assets of Atatürk Forest Farm – whose universalisation has been noticeably postponed – and the heritage of ideas bequeathed to future generations in the form of the forest and farm